Mesenchymal Stem Cells Secretions Enhanced ATP Generation on Isolated Islets during Transplantation. Issue 1 (31st December 2022) - Teratani, Takumi; Kasahara, Naoya; Fujimoto, Yasuhiro; Sakuma, Yasunaru; Miki, Atsushi; Goto, Masafumi; Sata, Naohiro; Kitayama, Joji
ABSTRACT: The success of islet transplantation in both basic research and clinical settings has proven that cell therapy has the potential to cure diabetes. Islets intended for transplantation are inevitably subjected to damage from a number of sources, including ischemic injury during removal and delivery of the donor pancreas, enzymatic digestion during islet isolation, and reperfusion injury after transplantation in the recipient. Here, we found that protein factors secreted by porcine adipose-tissue mesenchymal stem cells (AT-MSCs) were capable of activating preserved porcine islets. A conditioned medium was prepared from the supernatant obtained by culturing porcine AT-MSCs for 2 days in serum-free medium. Islets were preserved at 4°C in University of Wisconsin solution during transportation and then incubated at 37°C in RPMI-1620 medium with fractions of various molecular weights prepared from the conditioned medium. After treatment with certain fractions of the AT-MSC secretions, the intracellular ATP levels of the activated islets had increased to over 160% of their initial values after 4 days of incubation. Our novel system may be able to restore the condition of isolated islets after transportation or preservation and may help to improve the long-term outcome of islet transplantation. Abbreviations: AT-MSC, adipose-tissue mesenchymal stem cell; Cas-3, caspase-3; DAPI, 4, 6-diamidino-2-phenylindole; DTZ, dithizone; ES cell, embryonic stem cell; FITC, fluorescein isothiocyanate; IEQ, islet equivalent; INS, insulin; iPS cell, induced pluripotent stem cell; Luc-Tg rat, luciferase-transgenic rat; PCNA, proliferating cell nuclear antigen; PDX1, pancreatic and duodenal homeobox protein-1; UW, University of Wisconsin; ZO1, zona occludens 1.